(untitled) (Journal of Philosophy Culture and Political Science, 2019)
In this article are given historical phases of issues of armament in the system of international relations. The role of Republic of Kazakhstan in settling this problem is given also. Deep attention is given to the initiatives of the President of Republic of Kazakhstan to provide nuclear security in the system of international relations. Keywords: nuclear weapon, threat, nuclear energy, security, summit.